2009
DOI: 10.1007/s00266-009-9318-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipoabdominoplasty: Revisiting the Superior Pull-Down Abdominal Flap and New Approaches

Abstract: Abdominoplasty is a very common procedure, especially for patients with abdominal laxness, striaes, and muscle rectus diastases. With the advent of liposuction 28 years ago, we can improve body contouring by treating lipodystrophies in the epigastric, flank, trochanteric, and buttocks areas. With the patient in a sitting position, we estimate the amount of skin to be resected and outline the extension of the inferior suprapubic incision by the inguinal groove extremities. Epidural anesthesia via catheter is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…[17] Due to the poor quality of skin if it failed to redrape later, the excess fold would appear ugly. This excessive excision prevented this possible unfavourable result.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Due to the poor quality of skin if it failed to redrape later, the excess fold would appear ugly. This excessive excision prevented this possible unfavourable result.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermolysis might have been caused by the blood flow and abdominal tension. Uebel has reported that epidermolysis occurs most commonly in patients with a history of smoking 5 . We believe that epidermolysis can be prevented by undermining the lower flap as little as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygenation postoperatively, and lung compliance markedly improved. tus muscle diastases and for women in the postpartum period 5,6 . In this report, we describe our performing ab- It is important to be aware of potential postoperative complications, including infection, skin!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, Uebel [ 28 ] reported a revision of the superior pull-down abdominal flap described in 1975 by Sinder [ 29 ]. This revision added tunnel dissection, preservation of the inguinal and axillary lymphatic trunks, and paraumbilical high-tension sutures, as we describe in our reports of HSTA [ 16 – 20 ] and in this article.…”
Section: Hstamentioning
confidence: 99%